Experimental And Mathematical Modeling Studies Of Liquid-Liquid Membrane Contactor - H. Susanto; I. G. Wenten (Dept. of Chemical Engineering, Diponegoro University, 2001)
Experimental and modeling studies of the effect of tempetarature on liquid-liquid membrane contactor (LLMC) have been done. The experiments were conducted by varying temperature of 25 up to 80 0C, cross flow velocity from 0.02 to 0.05 m/s and feed concentration of 0, 5000 and 30,000 mg/l. In these experiments microporous hydrophobic hollow fiber polypropylene membrane with 0.2 μm was used as a contacting device. The modeling has been done by compiling mathematic equation of mass and heat transfers in liquid-liquid membrane contactor. Both the experimental and modeling result show, the increase in feed temperature increase the flux of pure water exponentially, whereas the flux decrease with increasing the permeate temperature. The feed temperature increase at higher temperature result in hogher flux increase. The concentration of pure water result in the range of 1.8 to 5.6 mg/l depending on feed concentration.Keywords : membrane contactor, modeling